Drying Kinetics of Leucaena esculenta Seeds Using a Solar Dryer - Angel Tlatelpa Becerro; Ramiro Rico Martínez; Guillermo Raúl Carbajal Pérez; Miriam Navarrete Procopio; Víctor Manuel Zezatti Flores; Erick Omar Castañeda Magadan; Samuel Portillo Contreras; Salvador Israel Avilés López; Erick César López-Vidaña (Energies)
The drying kinetics and physical and chemical characteristics of Leucaena esculenta seed drying using a forced convection solar dryer are described. The drying kinetics behavior is examined for three experiments under climate conditions of three different winter days in central Mexico, observing significant effects related to the reported pH levels of the seeds with values of 6.34, 5.98, 5.97, 5.82, and 6.07. The airflow measurements inside the drying chamber were observed, including the geometric dimensions, color, appearance, weight, and moisture loss, and the effective diffusivity coefficient <semantics><mfenced separators="|">Deff</mfenced></semantics> of Leucaena esculenta with values between 1.23 × 10−7 and 8.09 × 10−9 <semantics><mstyle scriptlevel="0" displaystyle="true">m2s</mstyle></semantics>. Solar drying, with the technology used in this study, is a viable alternative to give added value to Leucaena esculenta. This study can be the basis for developing alternatives to preserve seeds for animal and human consumption.